2022
DOI: 10.3389/fcell.2022.857230
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid is Required for Normal Morphogenetic Movements During Gastrulation

Abstract: Retinoic acid (RA) is a central regulatory signal that controls numerous developmental processes in vertebrate embryos. Although activation of Hox expression is considered one of the earliest functions of RA signaling in the embryo, there is evidence that embryos are poised to initiate RA signaling just before gastrulation begins, and manipulations of the RA pathway have been reported to show gastrulation defects. However, which aspects of gastrulation are affected have not been explored in detail. We previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 91 publications
1
5
0
Order By: Relevance
“…These results were further supported by analysis of the pax8 expression pattern which has a very dynamic and informative expression pattern around NF19 ( Heller and Brändli, 1999 ), indicating that experimental and control embryos are at approximately the same developmental stage during NTC stages ( Figures 1F–J’ ). These data demonstrate, as previously described, that the reduction of RA signaling by EtOH exposure induces a transient developmental delay that is overcome during early neurula stages ( Yelin et al, 2007 ; Gur et al, 2022b ), and the NTDs observed in the EtOH-treated embryos are not the result of a developmental delay.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…These results were further supported by analysis of the pax8 expression pattern which has a very dynamic and informative expression pattern around NF19 ( Heller and Brändli, 1999 ), indicating that experimental and control embryos are at approximately the same developmental stage during NTC stages ( Figures 1F–J’ ). These data demonstrate, as previously described, that the reduction of RA signaling by EtOH exposure induces a transient developmental delay that is overcome during early neurula stages ( Yelin et al, 2007 ; Gur et al, 2022b ), and the NTDs observed in the EtOH-treated embryos are not the result of a developmental delay.…”
Section: Resultssupporting
confidence: 89%
“…Previously we showed that the embryo is most sensitive to alcohol exposure close to the onset of gastrulation ( Yelin et al, 2005 ; Gur et al, 2022a ; Gur et al, 2022b ). In order to determine the sensitivity window for NTC defect induction by reduced RA signaling, we treated embryos with either EtOH or DEAB starting the treatments at different developmental stages.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reduced percent epiboly is indicative of a delay in the gastrulation process, in this case, probably caused by citral and thymol action. Citral is commonly used in pharmacology as an inhibitor of retinoic acid biosynthesis [24]. This acid plays a fundamental role in regulating early embryogenesis, especially during gastrulation and development of axis and limb formation [25].…”
Section: Discussionmentioning
confidence: 99%